2003
DOI: 10.14411/fp.2003.035
|View full text |Cite
|
Sign up to set email alerts
|

Four new species of Cichlidogyrus (Monogenea: Ancyrocephalidae), gill parasites of Tilapia cabrae (Teleostei: Cichlidae), with discussion on relative length of haptoral sclerites

Abstract: Tilapia cabrae Boulenger, 1899, a cichlid fish from coastal lowlands of the Republic of Congo (Africa), was examined for gill parasites. Four new species of the Monogenea were found, all belonging to Cichlidogyrus (Ancyrocephalidae): C. berradae sp. n., C. revesati sp. n., C. legendrei sp. n., and C. lemoallei sp. n. A possible relationship between the relative size of haptoral sclerites (i.e., uncinuli compared to gripi) and microhabitat selection in the studied host-parasite model is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 11 publications
2
56
0
Order By: Relevance
“…These values are higher than those found by Ueda et al (1997) in Nile tilapia grown in captivity and close to the levels reported by Tavares-Dias et al (2000) for redflowered tilapia in captivity. Ranzani-Paiva et al (2000) found a significant decrease in hematocrit values in Prochilodus lineatus (Valenciennes, 1836) from the Parana River which were infested by Dactylogyridae.…”
Section: Results An Results An Results An Results and Dmentioning
confidence: 96%
See 4 more Smart Citations
“…These values are higher than those found by Ueda et al (1997) in Nile tilapia grown in captivity and close to the levels reported by Tavares-Dias et al (2000) for redflowered tilapia in captivity. Ranzani-Paiva et al (2000) found a significant decrease in hematocrit values in Prochilodus lineatus (Valenciennes, 1836) from the Parana River which were infested by Dactylogyridae.…”
Section: Results An Results An Results An Results and Dmentioning
confidence: 96%
“…Studies by Pool and Chubb (1987) showed that monogeneans cause the death of the host when present on the gills in high numbers. Most monogeneans have a well-defined yearly infection pattern, where there is an increase in prevalence and intensity during the summer and a decline during the cold months until a minimum is reached in the spring.…”
Section: Results An Results An Results An Results and Dmentioning
confidence: 99%
See 3 more Smart Citations